Mythical symbolism in the structure of metatext - Aimukhambet, Ж.; Karakhankyzy , Ұ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article discusses the concept of modern research myth. A particular attention is paid to its symbolic nature. The definition of myth is analyzed as well as conclusions on the role of symbols in the structure of myth are systematized. Thus the basics of considering its allegorical and informational function in the context of metatextuality are proposed in the article. There is analysis of works which contain the opinions of mythological scholars where they explain the essence of the symbol. Particular importance in the work is attached to the thesis that the symbol is the most basic attribute of the myth. The importance of the metatext in explaining the symbolism is proved and the need for its analysis in this direction is substantiated. Conclusions about the features and functions of the metatext based on conclusions about intertextual links are given by the author, foundations of the interconnected consideration of myth are defined as ancient and new texts. The object of the analysis was specific examples of ancient myths, folklore works and fiction. The reign of water, which, in its mythical representation, connects this world with another world, is considered as a character transporting the human soul